Antifungal Activity of Bilimbi Leaves (Averrhoa bilimbi l.) Ethanol Extract on the Growht of Aspergillus flavus and Trichophyton mentagrophytes - Sari, Melia; Leny; Parhan; Mahara, Rifanzi (Universitas Muhammadiyah Prof. Dr. Hamka, 2024)
Background: Indonesia is a tropical region with high temperatures and humidity, which makes it prone to skin infections; this condition is very favorable for the growth of fungi on the skin. Starfruit is a plant that has the potential to be a cure for various diseases and is used as a supplement to maintain health. Starfruit leaves (Averrhoa bilimbi L.) are antimicrobial, anticancer, and antioxidant. This study aimed to see the inhibitory activity of Starfruit leaf extract against the growth of Aspergillus flavus and Trichophyton mentagrophytesfungi. Method: Belimbig leaves are extracted using the maceration method, and phytochemical screening is then carried out. Antibacterial testing using a healthy diffusion method. The concentration of extracts ranges from 10% to 40% for positive control, which is ketoconazole, and negative, using DMSO. Results: Screening results of extracts showed positive for flavonoids, alkaloids, saponins, tannins, and steroids. Ethanol extracts of Starfruit leaves (Averrhoa bilimbi L.) at concentrations of 10, 20, 30, and 40% inhibited the growth of Aspergillus flavus 12.25±1.30, 13.1±0.77, 13.4±0.68 and 14±3.61 and Trichophyton mentagrophytes13.1±1.79, 14.7±1.64, 15.4±2.16, and 18.3±2.89. The inhibitory power of ketoconazole against Aspergillus flavus and Trichophyton mentagrophytesis 23±0.877 and 30.1±0.45. Conclusion: Starfruit leave ethanol extract (Averrhoa bilimbi L.) has antifungal activity against Aspergillus flavus ATCC 3631 and Trichophyton mentagrophytesATCC 9533 with strong category.